Anti-VEGF treatment for myopic choroid neovascularization: from molecular characterization to update on clinical application - Zhang Y; Han Q; Ru Y; Bo Q; Wei RH (Dove Medical Press, 2015)
Yan Zhang,1 Qian Han,2 Yusha Ru,1 Qiyu Bo,1 Rui Hua Wei1 1Tianjin Medical University Eye Hospital, Tianjin Medical University Eye Institute, College of Optometry and Ophthalmology, Tianjin Medical University, Tianjin, 2Tangshan Eye Hospital, Tangshan, Hebei Province, People’s Republic of China Abstract: Choroidal neovascularization (CNV) secondary to pathologic myopia has a very high incidence in global, especially in Asian, populations. It is a common cause of irreversible central vision loss, and severely affects the quality of life in the patients with pathologic myopia. The traditional therapeutic modalities for CNV secondary to pathologic myopia include thermal laser photocoagulation, surgical management, transpupillary thermotherapy, and photodynamic therapy with verteporfin. However, the long-term outcomes of these modalities are disappointing. Recently, intravitreal administration of anti-VEGF biological agents, including bevacizumab, ranibizumab, pegaptanib, aflibercept, and conbercept, has demonstrated promising outcomes for this ocular disease. The anti-VEGF regimens are more effective on improving visual acuity, reducing central fundus thickness and central retina thickness than the traditional modalities. These anti-VEGF agents thus hold the potential to become the first-line medicine for treatment of CNV secondary to pathologic myopia. This review follows the trend of “from bench to bedside”, initially discussing the pathogenesis of myopic CNV, delineating the molecular structures and mechanisms of action of the currently available anti-VEGF drugs, and then systematically comparing the up to date clinical applications as well as the efficacy and safety of the anti-VEGF drugs to the CNV secondary to pathologic myopia. Keywords: formation of new vessels, choroid membrane, pathologic myopia, vascular endothelial growth factor, molecular mechanisms, clinical trials